EFEKTIFITAS MEDIA WANGI (WAYANG ANAK NEGERI INDONESIA) TERHADAP PERKEMBANGAN KEMAMPUAN BERBICARA ANAK DI TAMAN KANAK-KANAK KARTIKA 1-63 PADANG - Manurung, Yolanda; Syafnita, Tisna; Suryana, Dadan; Yulsyofriend (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of group role-play (storytelling) activities using WANGI (Wayang Anak Negeri Indonesia) media on the development of speaking skills in early childhood at Kartika 1-63 Kindergarten, Padang City. A quantitative approach with a quasi experimental method was used, namely a nonequivalent pretest-posttest control group design. Subjects consisted of 26 children of group B selected through purposive sampling, with group B1 (13 children) as the experimental class and group B2 (13 children) as the control class. Data were collected using a checklist performance test covering six speaking indicators: articulation, fluency, vocabulary, sentence structure, courage, and story comprehension. All items were valid and reliable (Cronbach Alpha > 0.60). The experimental class received four sessions of group role-play using WANGI media, while the control class used a conventional storybook. The pretest mean of the experimental class increased from 8.77 to 19.15 at posttest, while the control class increased from 7.46 to 13.92. The Independent Sample t-Test on Gain Scores showed t = 3.690, df = 24, significance 0.001 (< 0.05), with a Cohen's d effect size of 1.45 (strong category). It is concluded that WANGI media is effective in developing the speaking skills of early childhood at Kartika 1-63 Kindergarten, Padang City.